Pattern of hygiene practices among health care workers during the COVID-19 pandemic: a tertiary health care experience from Central Kerala - John, Susan; Subrahmanian, Suremya A.; Xavier, Rina T. (International Journal Of Community Medicine And Public Health, 2021)
Background: The recent COVID-19 pandemic has highlighted the relevance of following hygiene practices across all sectors of healthcare workers. Disparities in the correct practices among clinical and para clinical cadres of HCWs predispose to increased risk of infection. A survey was conducted to assess the hand and respiratory hygiene practices across the hospital. Methods: A cross sectional survey was conducted through a self-administered questionnaire across an online platform with questions on hand hygiene, mask and surface contamination related practices. Staff were grouped as clinical and para clinical for comparison of these practices. Results: Among the 501 respondents, 83.4% were females with a mean age of 30.78±8.48 years. Nursing staff were the majority (57.88%) followed by nonclinical and para clinical staff (20.77%). Of the study population, 96.6% performed hand wash and 97.2% refrained from giving handshakes in the previous hour. Over 60% maintained proper face mask practices. Undoing the lower tie of the mask first, was answered by 76.67% while 7.2% felt the sequence was irrelevant. Touching common surfaces were avoided by 46.3% of them, while 95% immersed their hospital attire in soap and water for 15 minutes. It was seen that a greater proportion of clinical staff had better practices when compared to para clinical and the difference statistically significant. There was no significant variation of practices with age. Conclusions: Focussed monitoring and motivation can help in improving hygiene practices among all cadres of HCWs.